Pomocniczość i zrównoważony rozwój — uwarunkowania aksjologiczne na przykładzie zagospodarowania przestrzennego gminy w Republice Włoskiej - Nowak, Joanna (Wydawnictwo Uniwersytetu Wrocławskiego, 2015)
The aim of this paper is to describe the axiological conditions of spatial development in Italy inthe light of two main principles of Italian administrative law: subsidiarity and sustainable development. The principle of subsidiarity after the constitutional reform of 2001 has been a fundament of administration system. Concurrently for example values of human dignity, property, common goods have a big influence on the processes of municipality spatial planning and land use management.
Keywords: Włochy; urbanistyka; pomocniczość; rozwój; aksjologia